2011
DOI: 10.1093/ecam/neq029
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Brazilian Propolis Microparticles against Yeasts Isolated from Vulvovaginal Candidiasis

Abstract: Propolis, a resinous compound produced by Apis mellifera L. bees, is known to possess a variety of biological activities and is applied in the therapy of various infectious diseases. The aim of this study was to evaluate the in vitro antifungal activity of propolis ethanol extract (PE) and propolis microparticles (PMs) obtained from a sample of Brazilian propolis against clinical yeast isolates of importance in the vulvovaginal candidiasis (VVC). PE was used to prepare the microparticles. Yeast isolates (n = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 45 publications
5
55
1
Order By: Relevance
“…It contains resinous substances collected by honey bees, from various plants, thus forming a complex of biologically active substances [16]. Several research groups revealed high antifungal potential of propolis against Candida clinical isolates [26][27][28][29]. The results of our investigation confirmed high fungicidal activity of propolis against all strains tested, but only in the case of one of four analyzed samples.…”
Section: Discussionsupporting
confidence: 72%
“…It contains resinous substances collected by honey bees, from various plants, thus forming a complex of biologically active substances [16]. Several research groups revealed high antifungal potential of propolis against Candida clinical isolates [26][27][28][29]. The results of our investigation confirmed high fungicidal activity of propolis against all strains tested, but only in the case of one of four analyzed samples.…”
Section: Discussionsupporting
confidence: 72%
“…These results suggest that Cuban propolis may possess a specific activity against Gram-positive bacteria, which was also observed for propolis from other geographical origins (Lofty 2006). In the literature, activity against C. albicans has also been reported for propolis samples from Brazil (Dota et al 2011), Thailand (Umthong et al 2009), Mexico (Quintero-Mora et al 2008) and Iran (Ghasem et al 2007). However, in our study, propolis samples did not show any activity against C. albicans, although there was an observed inhibitory effect against T. rubrum.…”
Section: Discussionmentioning
confidence: 92%
“…The two colorectal cancer cell lines responded well under the treatments. However, HCT-116 cells were generally found more susceptible compared to HT-29 cells with the IC50 values of crude extract, 2 and 3 for HCT-116 lower (IC50 = 1.410, 2.279, 3.013 µg/mL, respectively) than HT-29 (IC50 = 5.620, 5.320, 5.359 µg/mL, respectively).…”
Section: Resultsmentioning
confidence: 94%
“…For many centuries, aside from its use as food, beverage and food supplement, it has long been used extensively in traditional medicine because of its wide range of therapeutic values for the treatment of common cold, flu, upper respiratory tract infections, as dermatological preparations for wounds, burns, acne, herpes simplex, genitalis and neurodermatitis, as mouthwash and toothpaste to prevent caries and gingivitis and for cosmetic applications [1,2]. Propolis was shown to exhibit a broad spectrum of biological activities which include antimicrobial [3,4], antifungal [5,6], free radical scavenging [7,8], anti-HIV [9,10], anti-inflammatory [11,12] and anti-herpes [13,14]. A recent study reported that propolis, at a concentration of 0.01 % (w/v), exhibited antiproliferative and cytotoxic actions against human fibroblasts proliferation in cell culture, followed by mild cell necrosis [15].…”
mentioning
confidence: 99%